RAINFALL AND WATER DEFICIT EFFECT ON OIL PALM PRODUCTION (Elaeis guineensis Jacq.): CASE STUDY IN TALISAYAN DISTRICT: PENGARUH CURAH HUJAN DAN DEFISIT AIR TERHADAP PRODUKSI KELAPA SAWIT (Elaeis guineensis Jacq.): STUDI KASUS DI KABUPATEN TALISAYAN - Sondang Lisnawati Nadapdap (Universitas Widya Gama Mahakam, 2024)
Global climate change has triggered changes in rainfall patterns in many regions, including increased rainfall intensity, longer periods of drought, and unpredictable weather fluctuations. This study aims to determine the effect of rainfall and water deficit on oil palm production. This study was carried out in Talisayan Estate, Cepuak and Dumaring Village, Talisayan District, Berau Regency, East Kalimantan Province, starting from October to November 2023. The analysis method uses correlation and regression analysis methods. Correlation analysis is used to determine the relationship between rainfall and oil palm production based on the data obtained, while regression analysis is used to determine how much influence rainfall has on oil palm production. To calculate the water deficit used Tailliez method. The result of this study is that rainfall affects oil palm production by 14.2% (α=0.05) and water deficit affects palm oil production by 3% (α=0.05).